2015
DOI: 10.1002/2014ja020663
|View full text |Cite
|
Sign up to set email alerts
|

Misidentification of the source of a neutron transient detected by MESSENGER on 4 June 2011

Abstract: Low‐energy (1–10 MeV) neutrons emanating from the Sun provide unique information about accelerated ions with steep energy spectra that may be produced in weak solar flares. However, observation of these solar neutrons can only be made in the inner heliosphere where measurement is difficult due to high background rates from neutrons produced by energetic ions interacting in the spacecraft. These ions can be from solar energetic particle events or produced in passing shocks associated with fast coronal mass ejec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…This task is necessary to answer the criticism of our analyses of the 31 December 2007 and 4 June 2011 neutron events given by Share et al . [, ]. Our methodology was first presented in Lawrence et al .…”
Section: Observations At Messengermentioning
confidence: 99%
See 3 more Smart Citations
“…This task is necessary to answer the criticism of our analyses of the 31 December 2007 and 4 June 2011 neutron events given by Share et al . [, ]. Our methodology was first presented in Lawrence et al .…”
Section: Observations At Messengermentioning
confidence: 99%
“…Before proceeding to a chronological analysis of the seven accepted neutron events, we present our methodology to fill the void in our knowledge of the energetic ion environment at MESSENGER by using the ion spectra measured at 1 AU by the energetic ion experiments on the STEREO A/B and the GOES/ACE spacecraft. This task is necessary to answer the criticism of our analyses of the 31 December 2007 and 4 June 2011 neutron events given by Share et al [ , 2015. Our methodology was first presented in Lawrence et al [2014] and later defended in Lawrence et al [2015b].…”
Section: Overview Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis, in part, of these results, Lawrence et al [2014] concluded that there was strong evidence that the detected neutrons were solar in origin. Share et al [2015] (hereafter shortened to Share et al) recently criticized Lawrence et al's [2014] study. In particular, Share et al concluded that the excess neutrons detected on 4 June 2011 were generated locally at the spacecraft.…”
Section: Introductionmentioning
confidence: 99%